Partial fishmeal replacement with poultry by-product meal and yeast enhances growth and health in Clarias gariepinus, while unbalanced PBM diets induce metabolic stress - Nader Iskandar Hamwi; Hamam Adib Altajer (PLoS ONE, 2026)
This study evaluates a dual dietary strategy in African catfish ( Clarias gariepinus ): optimizing fishmeal replacement and assessing unbalanced, low-cost feeding risks. Five diets were tested over 12 weeks: four isonitrogenous diets (T1–T4, 35% crude protein) with graded fishmeal replacement using poultry by-product meal (PBM) and brewer’s yeast ( Saccharomyces cerevisiae ), and one unbalanced diet (T5, 100% PBM without carbohydrates, lipids, or micronutrients). A total of 125 fish (initial weight 47.49 ± 0.18 g) were distributed across five 1 m³ tanks (25 fish/tank; n = 1 tank/diet) and fed twice daily at 3% body weight. Growth, hepatic enzymes [alanine/aspartate aminotransferase (ALT/AST)], cholesterol, and hematological parameters [hemoglobin (Hb), hematocrit (Hct), lymphocytes] were measured. Fish fed T2 (15% fishmeal, 20% PBM, 5% yeast) showed the highest daily weight gain (4.36 ± 0.02 g/day), best feed conversion ratio (FCR = 1.32), lowest ALT (18.53 ± 0.37 U/L) and AST (22.09 ± 0.45 U/L), reduced cholesterol (135.53 ± 2.37 mg/dL), and highest Hb (10.89 ± 0.37 g/dL) and Hct (28.76 ± 0.91%). Conversely, T5-fed fish exhibited poor growth (1.97 ± 0.03 g/day), elevated hepatic enzymes, increased cholesterol, and hematological signs of impaired erythropoiesis and chronic immune activation. Diets T3 and T4 showed intermediate performance. Strong negative ( r = −0.99) and positive ( r = +0.98) correlations linked daily weight gain with ALT and Hct, respectively. These findings indicate that protein quality and dietary balance outweigh crude protein content for fish health and performance. Combining moderate fishmeal with PBM and yeast offers a sustainable strategy to reduce fishmeal reliance, whereas the 100% PBM diet highlights risks of unbalanced feeds in resource-limited settings. These results provide preliminary evidence supporting strategic fishmeal replacement, underscoring the need for validation in fully replicated trials.